PARENTING PATTERNS OF PARENTS AND MENTAL-EMOTIONAL DEVELOPMENT IN TAMAN KANAK-KANAK DHARMA WANITA GODEAN, NGANJUK DISTRICT - Rahayu Budi Utami; Amrina Rosada (Nurse and Health: Jurnal Keperawatan, 2018)
Background: Growth and development on preschooler is the basic step that influenced the next development on their life thus it was called golden period. Preschooler’s psychosocial development related on their mental process. One of the factor that influenced mental-emotional development is the lacked of parenatal affection or warmth and care to the children.Objectives: This study aimed to describe and examine the correlation between parenting patterns and mental-emotional development at Taman Kanak-kanak Dharma Wanita Godean, Nganjuk District.Method: Correlation method with case control approched was utilized on this research and implemented on March 27th of 2018 throughout March 29th of 2018 at Taman Kanak-kanak Dharma Wanita Godean Kabupaten Nganjuk. All preschoolers parents as many as 47 couple (94 people) at this Taman Kanak-kanak Dharma Wanita Godean Kabupaten Nganjuk was defined as the population sampling. This research utilized purposive sampling thus as many as 40 parents matched the inclusion and exclusion criteria. The parenting was independent variable and the mental-emotional development was the dependent variable. Statistical test used Spearmen Rho test.Results: The outcome of the study was found that most parenting parents of 23 parents (57,5 %) had an authoritative parenting type, most of which were 23 elderly (57,5 %) was uneble to development mental-emotional approach and nearly half of the 18 parents (45 %) have authoritative parenting style and unable to develop mental-emotional approach, alternate hypothesis (Ha) is accepted with rho value of 0,011 less than alpha value of 0,05 (rho= 0,001 ≤ α= 0,05).Conclusion: Appropriate parenting corresponds child’s growth and influenced mental-emotional child’s development, parenting efficacy can be utilized for preventive measure on preschooler mental-emotional disorder. Key words: Parenting, Mental-emotional development, Preschooler.